Nasopharyngeal Pneumococcal Colonization Density Is Associated With Severe Pneumonia in Young Children in the Lao People's Democratic Republic. (11th May 2021) - Carr, Olivia J J; Vilivong, Keoudomphone; Bounvilay, Laddaphone; Dunne, Eileen M; Lai, Jana Y R; Chan, Jocelyn; Vongsakid, Malisa; Changthongthip, Anisone; Siladeth, C; Ortika, Belinda; Nguyen, Cattram; Mayxay, Mayfong; et al.
Abstract: Background: No studies have explored the association between pneumococcal nasopharyngeal density and severe pneumonia using the World Health Organization (WHO) 2013 definition. In Lao People's Democratic Republic (Lao PDR), we determine the association between nasopharyngeal pneumococcal density and severe pneumonia in children. Methods: A prospective observational study was undertaken at Mahosot Hospital, Vientiane, from 2014 to mid-2018. Children <5 years admitted with acute respiratory infections (ARIs) were included. Clinical and demographic data were collected alongside nasopharyngeal swabs for pneumococcal quantification by lytA real-time quantitative polymerase chain reaction. Severe pneumonia was defined using the 2013 WHO definition. For pneumococcal carriers, a logistic regression model examined the association between pneumococcal density and severe pneumonia, after adjusting for potential confounders including demographic and household factors, 13-valent pneumococcal conjugate vaccine status, respiratory syncytial virus co-detection, and preadmission antibiotics. Results: Of 1268 participants with ARI, 32.3% (n = 410) had severe pneumonia and 36.9% (n = 468) had pneumococcal carriage. For pneumococcal carriers, pneumococcal density was positively associated with severe pneumonia (adjusted odds ratio, 1.4 [95% confidence interval, 1.1–1.8]; P  = .020). Conclusions: Among children with ARIs and pneumococcal carriage, pneumococcal carriage density was positively associated with severe pneumonia in Lao PDR. Further studies may determine if pneumococcal density is a useful marker for pneumococcal conjugate vaccine impact on childhood pneumonia. Abstract : No studies have explored the association between pneumococcal nasopharyngeal density and severe pneumonia using the World Health Organization 2013 definition. Among children with acute respiratory infections and pneumococcal carriage, pneumococcal carriage density was positively associated with severe pneumonia in Laos.